We made this bed … now look who's lying in it. (November 2018) - Spector, Bert; Wilson, Suze
In considering the 'Populist Responses to Austerity and Cultural Change: Brexit, Trumpism and Beyond', there is a temptation, even a degree of comfort, in depicting 2016 as a kind of deviant moment in which non-elite anger and anxiety fueled an outburst of anti-progressive energy and the electoral victory of demagogues. The proposition put forth in this essay is that leadership scholarship is itself culpable. Transformational leadership, the dominant theme of that discourse, relies on the individual leader as an exceptional individual capable, even obliged, to reshape the worldview of followers in order to align them with the leader's approach. By favoring an appeal to emotions over a rational exchange of positions, by assuming the superiority of one set of values over any others, by denying the validity of differing and/or conflicting interests, and by asserting authority based on hierarchical position rather than informed choice and consent, transformational leadership veered closely to our understanding of demagogues. Unintended though it may be, the dominant discourse becomes engrained as a 'regime of truth' into a pervasive, highly problematic social norm. Leadership scholars must accept a degree of responsibility and reconsider romantic notions of leadership in order to advance alternatives, not only to Trump and his particular agenda but also to the problematic assumptions embedded in and wider effects entwined with leadership thought.